The Impact of Islamic Banking Growth and Development on Public Trust in Indonesia - Zulkarnain, Zulkarnain; Arif, Zainal (El-kahfi | Jurnal Ekonomi Islam, 2025)
The development of Islamic banking in Indonesia has shown significant progress, yet public trust remains a critical determinant for its sustainable growth. This study investigates the influence of Islamic banking growth and development on public trust, focusing on three key dimensions: digital innovation, asset growth, and financing expansion. The objective is to determine which factors most strongly affect trust and how this trust impacts customer loyalty and preference toward Islamic financial institutions. Using a quantitative survey method, data were collected from 400 respondents across various regions in Indonesia who are users or observers of Islamic banking services. The research employed statistical analysis techniques including descriptive statistics, classical assumption tests, and multiple linear regression analysis to examine relationships among the variables. The findings reveal that digital innovation has the most significant positive impact on public trust, followed by asset growth and financing performance. Trust, in turn, mediates customer loyalty and preference for Islamic banking. The study also finds that consistency in applying Shariah-compliant practices enhances credibility and long-term engagement with customers. This study contributes to the literature on Islamic banking by integrating Islamic ethical perspectives, including references from the Qur'an and Hadith, into the discourse on financial trust. Practically, the results highlight the importance of technological innovation and value-based service delivery in strengthening trust in Islamic banking institutions. The study recommends continuous investment in digital platforms, ethical financing models, and transparent communication strategies to improve trust and institutional sustainability.